Pengaruh Customer Relationship Management (CRM) dan Service Quality terhadap Customer Loyalty Melalui Customer Satisfaction Pelanggan Indomaret : (Studi Kasus Pelanggan Indomaret DKI Jakarta) - Octia Dea Ayu Amanda; Andi Muhammad Sadat; Rahmi Rahmi (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The purpose of this study is to determine the effect of Customer Relationship Management (CRM) and Service Quality on Customer Loyalty and Customer Satisfaction in the study of Indomaret customers in DKI Jakarta. This research uses SEM (Structural Equation Modeling) for quantification. The data collected was obtained through distributing questionnaires using Google Form with a purposive sampling method with certain criteria. The characteristics of this research sample are customers who have shopped at Indomaret. Data analysis was carried out using SmartPLS version 4.0 software and the sample selected to test all variables was 120 participants. The results showed that CRM has a significant effect on Customer Loyalty, Service Quality has a significant effect on Customer Loyalty, CRM has a significant effect on customer satisfaction. Service Quality has a significant effect on Customer Satisfaction, Customer Loyalty has a significant effect on customer satisfaction, CRM has a significant effect on Customer Loyalty through Customer Satisfaction, Service Quality has a significant effect on Customer Loyalty through Customer Satisfaction.